Allosteric HIV‐1 integrase inhibitors promote aberrant protein multimerization by directly mediating inter‐subunit interactions: Structural and thermodynamic modeling studies. (17th August 2016) - Deng, Nanjie; Hoyte, Ashley; Mansour, Yara E.; Mohamed, Mosaad S.; Fuchs, James R.; Engelman, Alan N.; Kvaratskhelia, Mamuka; Levy, Ronald
Abstract: Allosteric HIV‐1 integrase (IN) inhibitors (ALLINIs) bind at the dimer interface of the IN catalytic core domain (CCD), and potently inhibit HIV‐1 by promoting aberrant, higher‐order IN multimerization. Little is known about the structural organization of the inhibitor‐induced IN multimers and important questions regarding how ALLINIs promote aberrant IN multimerization remain to be answered. On the basis of physical chemistry principles and from our analysis of experimental information, we propose that inhibitor‐induced multimerization is mediated by ALLINIs directly promoting inter‐subunit interactions between the CCD dimer and a C‐terminal domain (CTD) of another IN dimer . Guided by this hypothesis, we have built atomic models of inter‐subunit interfaces in IN multimers by incorporating information from hydrogen‐deuterium exchange (HDX) measurements to drive protein‐protein docking. We have also developed a novel free energy simulation method to estimate the effects of ALLINI binding on the association of the CCD and CTD. Using this structural and thermodynamic modeling approach, we show that multimer inter‐subunit interface models can account for several experimental observations about ALLINI‐induced multimerization, including large differences in the potencies of various ALLINIs, the mechanisms of resistance mutations, and the crucial role of solvent exposed R‐groups in the high potency of certain ALLINIs. Our study predicts that CTD residues Tyr226, Trp235 and Lys266 are involved in the aberrant multimer interfaces. The key finding of the study is that it suggests the possibility of ALLINIs facilitating inter‐subunit interactions between an external CTD and the CCD‐CCD dimer interface.